Políticas de recursos humanos da Fundação Instituto Brasileiro de Geografia e Estatística (IBGE) e a elevação da faixa etária média de seus servidores - Rocha, Carla Rodrigues (2010)
This study aimed to understand the expectations of the servers of the Instituto Brasileiro de Geografia e Estatística (IBGE) in relation to human resources policies, given the increased age of the population of the servers that institution. It took as its starting point the results of surveys of IBGE - Demographic Census and the National Household Sample Survey - that have demonstrated over the years the trend of increased life expectancy of the population. This trend is reflected in the increase of average age of workers within this institution. Also, consider the changing role of the Area of Human Resources over the years and its importance within the Brazilian public administration, as always had a prominent place in several administrative reforms implemented. Thus, based on three vectors: increased life expectancy of the Brazilian, human resources management and public administration in Brazil, identified as the IBGE and their servers have experienced the reality of a cadre of increasingly older. The interviews with the officers, analyzed by the method of content analysis revealed that the issue of aging, despite strong reflections within the institution, it is still not clearly highlighted within the human resource policies, which makes the servers fail to perceive HR policies focused on the aging of the table, being discouraged and disappointed about the topic and at the same time eager to clear and radical changes with respect to management of HR policies.